A comunicação homem-animal numa fazenda de Minas Gerais - Couto, Hildo Honório do (Cadernos de Linguagem e Sociedade, 2010)
The purpose of this paper is to analyse man-animal çommunication, a widespread phenomenon on farms. There are specific expressions for each kind of animal (dogs, cats, cows, chickens, etc), ali of them highly context-bound. Thus, pragmatic (kinesic, proxemic) aspects play an important role in this kind of communication. Finally, suggestions are made about some possible "universals of communication".